Jérôme Deyris, De la stabilité des prix à la stabilisation du climat ? L’économie politique du verdissement des banques centrales - Jérôme Deyris (Revue de la Régulation)
My thesis combines three theoretical approaches to analyse the rise of green central banking: the political economy of varieties of capitalism, the economic sociology of organisations and bureaucracy, and the evolutionary theory of institutional change. I show that while the type of greening, its translation into instruments and the ways in which it is legitimised all depend on the institutional context in which the central bank is embedded, this relationship is less strict and less unidirectional than it might seem. Indeed, the institutional framework gives central bankers considerable leeway. This room for manoeuvre leads to significant internal conflicts, and to the formation of coalitions with different types of external players with divergent interests. The outcome of this power struggle then in turn influences the trajectory of economic development, by gradually reconfiguring the central bank’s place in the governance of finance.